MO259LYMPHOPENIA AT ANCA-GLOMERULONEPHRITIS DIAGNOSIS IS CORRELATED WITH SEVERITY AND RENAL PROGNOSIS. (29th May 2021) - Wacrenier, Samuel; Riou, Jeremie; Jourdain, Pierre; Guibert, Fanny; HENRY, NICOLAS; Assia, DJEMA; Coindre, Jean Philippe; Crochette, Romain; Cousin, Maud; Croue, Anne; Jean François, SUBRA; Piccoli, Giorgina; et al.
Abstract: Background and Aims: Lymphopenia is commonly observed in various autoimmune diseases, such as systemic lupus erythematosus, where it has been associated with disease activity or prognosis. However, in ANCA-associated vasculitis (AAV) only few, small-scale studies have been targeted to this issue. Research has not yet focused on ANCA-glomerulonephritis (ANCA-GN) patients. Thus, the aim of this study was to analyze the association between lymphocyte counts and outcomes in a large cohort of ANCA-GN patients. Method: We used the Maine-Anjou AAV registry that retrospectively gathers data on consecutive patients affected by AAV in four French Nephrology Centers, recorded since January 2000. We analyzed clinical, biological, and histological data at diagnosis of ANCA-GN. Biological data, including lymphocyte counts, were collected before the administration of any immunosuppressive treatment. Risk factors for end-stage kidney disease (ESKD) were analyzed. Event-free survival was also assessed. Results: Among the 145 patients included in the study, 53 (37%) patients presented with lymphopenia at ANCA-GN diagnosis. Lymphopenic patients were older (72 [63–79] vs 66 [56–73] years old, p = 0.010), had a lower renal function at baseline (eGFR 13 mL/min vs 26 mL/min, p = 0.002), and a higher proteinuria (1.86 [1.21–3.52] g/g vs 1.30 [0.75–2.65] g/g, p = 0.042). There was a trend for a higher BVAS (18 [14–22] vs 15 [12–20], p = 0.076) in lymphopenic patients. Therapeutic management between the two groups was similar. There was no difference in relapse rate between the two groups but lymphopenic patients were more likely to require kidney replacement therapy (51% vs 25%, p = 0.003) and were more likely to die (34% vs 17%, p = 0.039). Lymphopenia was correlated with histological lesions and especially with the percentage of sclerotic glomeruli (p = 0.0027). ESKD-free survival and overall survival were lower in lymphopenic patients (p < 0.0001 and 0.0051 respectively). In multivariate Cox analysis, lymphopenia, but not death, was an independent risk factor for ESKD (HR 4.47 (95% confidence interval: [2.06–9.72], p < 0.001). Conclusion: Lymphopenia correlates with severity of ANCA-GN at diagnosis and predicts poor renal outcome. In this view, lymphopenia could be used as a simple and cost-effective biomarker to assess renal prognosis at ANCA-GN diagnosis.